Seasonal differences in egg size in three species of crabs from a tropical upwelling zone. Issue 3 (16th March 2018) - Collin, Rachel; Nieto, Nerea; Peña, Cynthia
ABSTRACT: Egg size and offspring size are fundamentally important aspects of the life histories of all animals. However the impact of environmental conditions on intraspecific variation in egg size of marine invertebrates is poorly documented. Here we followed three species of intertidal crabs Xanthodius sternberghii, Petrolisthes armatus and Clibanarius albidigitus to understand how seasonal environmental variation in temperature and salinity associated with seasonal upwelling impacts egg size. Ovigerous females of both P. armatus and C. albidigitus were found year round, while X. sternberghii has a limited reproductive season, with ovigerous females found only between November and February. In all three species more than half of the variation in egg size was attributable to variation among broods from different females. Eggs collected during the dry, upwelling season were significantly larger than those collected during the wet, non-upwelling season. Multiple regression analysis showed that average egg size from each brood was significantly negatively correlated with temperature for all three species. Egg size was also negatively correlated with salinity in P. armatus when we controlled for temperature. Overall these results support the idea that changes in environmental temperature caused by seasonal upwelling play a significant role in generating seasonal differences in egg size.